Reflection of Islamic Civilization History in English Language Teaching: A Humanistic and Spiritual Approach - Wahyu Wijayati; Sabil Mokodenseho (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Motivation in English language learning remains a critical factor for achieving effective outcomes, yet integrating cultural, ethical, and spiritual values is often overlooked in contemporary education. Previous studies highlight the importance of humanistic and spiritual approaches, but limited research connects English learning with Islamic civilization history to enhance students’ motivation. This study aims to explore how reflections on Islamic civilization, combined with humanistic and spiritual approaches, can enrich English language learning. A qualitative descriptive method was employed, using literature review and document analysis as data sources. Findings indicate that integrating Islamic civilization values increases students’ cultural awareness, moral understanding, and intrinsic motivation, while humanistic and spiritual dimensions foster self-confidence, ethical awareness, and holistic development. The study concludes that such integration produces meaningful and transformative learning experiences. It is recommended that English teaching incorporate historical, ethical, humanistic, and spiritual elements to improve student engagement, linguistic proficiency, and character development.